Power bob lock, charge & leave / Nur Syafirah Saari …[et al.] - Saari, Nur Syafirah; Mohd Kamaluddin, Nor Sofiah; Malek Fesal, Nur Marini; Mat Ghani, Nuraina Mardia; Che Zakaria, Zafirah Noor (2016)
Power Tech Sdn. Bhd. was established on January 2017. Our business is based on the production of charging vendor machine called Power Bob. Power Tech was registered and headquartered in Bangi, Selangor. We are Malaysian and dedicated to the Malaysian consumers especially all costumer in shopping mall. The invention of the product idea are came across our mind after we find out difficult to find to charger mobile phone when battery are flat suddenly in the middle of shopping mall and people feel heavy to bring the power bank. Thus, we want to pi vose that we sell a service that can ones can charge their phone and leave for sho] | dn :; and do their own activities. The main product that we invented is service of charging vendor machine. The product is operating by a simple system by just put some amount of money and their phone, then the machine will lock and release the safety card. By using this product, we do not need powerbank to charge m phone. We have decided that our commercialize research and development is licensing a patent because the patent of product is made by company while the m u< =facture are given the exploitation right to produce. On the other hand, our product's intellectual property is industrial design because the design is new in Malaysia.